Optical properties of metallic nanoparticles and perspectives for biomedical applications - FAROOQ, Sajid (2018)
This thesis explains some of the fundamental concepts regarding localized surface plasmon resonance (LSPR) and how to explore it on biosensing and photodynamic therapy. Molecular LSPR sensing and metal-enhanced oxygen singlet generation for photodynamic therapy were demonstrated exploring spherical and non-spherical silver/gold nanoparticles with various size and structures. Mathematical simulations and experimental analyses were used on the discussion of the metallic nanoparticle (NP) size, material and shape contribution to LSPR-based effects. The light-NP interactions were evaluated by the use of Finite Element Method with COMSOL Multiphysics. Computational simulations, focused on the assessment of the LSPR spectrum and spatial distribution of electromagnetic field enhancement near a metallic nanoparticle, were used to ascribe the behavior of crucial parameters, as figure of merit, bulk and molecular sensitivity, which rules the LSPR sensor performance. Here, spherical nanostructures were evaluated as starting points for LSPR biosensor. The theoretical analyses indicated a nonlinear behavior of the bulk and molecular sensitivity of gold and silver nanosphere-based sensing platform as function of the NP size. Significant LSPR peak shift due to the adsorption of molecular layer on the NP surface were observed for nanoparticles with ~ 5 and ~ 40 nm radii. Besides, the theoretical approach used in this work provides insights on the LSPR behavior due to adsorption layer of molecules on a NP surface, establishing a new paradigm on engineering LSPR biosensor. Moreover, molecular sensing was demonstrated by the identification Candida albicans antigen. The feasibility of using Ag nanotriangles on LSPR biosensing was also evaluated. Refractive index based sensitivity (406 nm/RIU) and figure of merit (2.6) values were calculated for nanotriangles colloids, with altitudes ~ 57 nm, and attributed to LSPR near field enhancement at the tips of the nanostructure. The interaction of Ag nanotriangles with Methylene blue photosensitizer was also appraised, and 2.2-fold metal enhanced singlet oxygen generation was determined. The association of Methylene blue with Au nanoshells (80 nm silica core/20 nm gold shell) was also quantified, showing 300% increase in singlet oxygen production upon the irradiation of laser light (632 nm). These results introduce new perspectives on the use of metallic nanoparticles on photodynamic process.